Modelling transmission systems in energy system analysis: A comparative study. (15th May 2020) - Gunkel, Philipp A.; Koduvere, Hardi; Kirkerud, Jon Gustav; Fausto, Felipe Junqueira; Ravn, Hans
Abstract: In order to comply with European emission goals, the role of accurate grid representation in energy system optimization is getting increasingly more important with larger shares of variable renewable energies. This paper compares the transmission system representation approaches using flow-based (FB) modelling with Power Transfer Distributing Factor (PTDF) to the Net Transfer Capacity (NTC) in energy system models for investment optimization. The open-source model Balmorel was used in order to investigate the impact on important modelling results. Overall, electricity prices flattened on a spatial level using FB modelling compared to NTC. Additionally, a change of investment decision in generation capacities is identified. Locations of newly installed lines and production sides are shifted furthermore slightly when representing the AC-system and its physics through FB modelling. However, a rough spatial representation and the subsequent clustering of the lines creates an uncertainty about the impact of overestimated line capacities and the benefits compared to NTC. Therefore, further studies are needed to accurately assess the impact of the transition from the current NTC to FB methodology in investment decision optimization. Highlights: Flow-based (FB) modelling changes grid operation compared to the NTC representation. Locations of generation and line expansion are slightly different with FB modelling. Modest shift in generation technologies investments. Spatial differences in electricity prices are smoothed out with FB modelling.